Er:YAG Laser and Fractured Incisor Restorations: An In Vitro Study - C. Fornaini; S. Petruzzella; R. Podda; E. Merigo; S. Nammour; P. Vescovi (Hindawi Limited, 2012)
Introduction. The aim of this study was to analyse the effects of an Er:YAG laser on enamel and dentine in cases of dental restorations involving fractured teeth, utilizing the dental fragment. Materials and Methods. Seventy-two freshly extracted bovine incisors were fractured at the coronal level by using a hammer applied with a standardized method, and the fragment was reattached by using three different methods: Er:YAG laser, orthophosphoric acid, and laser plus acid. The different groups were evaluated by a test realized with the dynamometer to know the force required to successfully detach the reattached fragment and by a microinfiltration test by using a 0.5% methylene blue solution followed by the optic microscope observation. Results. The compression test showed only a slight difference between the three groups, without any statistical significance. The infiltration test used to evaluate the marginal seal between the fracture fragment and the tooth demonstrated that etching with Er:YAG laser alone or in combination with orthophosphoric acid gives better results than orthophosphoric acid alone, with a highly significant statistical result. Discussion. Reattaching a tooth fragment represents a clinically proven methodology, in terms of achieving resistance to detachment, and the aim of this work was to demonstrate the advantages of Er:YAG laser on this procedure. Conclusion. This "in vitro" study confirms that Er:YAG laser can be employed in dental traumatology to restore frontal teeth after coronal fracture.